2002
DOI: 10.1001/archotol.128.3.237
|View full text |Cite
|
Sign up to set email alerts
|

Hürthle Cell Tumors

Abstract: Hürthle cell neoplasms can now be classified using histopathological as well as molecular criteria. It appears that the new subclassification of malignant HCTs into follicular (HCC) and papillary (HCPTC) variants identifies 2 distinct biological groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(4 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The diagnosis of oncocytic follicular adenoma has been questioned, since some authors have found that oncocytic follicular lesions called benign subsequently behave in a malignant fashion (20). This may be attributed to failure to recognize the nuclear atypia of malignancy in these neoplasms (12,18,21,22), but also partly to common challenges in the identification of invasive growth in follicular neoplasms (23)(24)(25)(26).…”
Section: Thyroid Follicular Nodular Disease and Adenomasmentioning
confidence: 99%
See 2 more Smart Citations
“…The diagnosis of oncocytic follicular adenoma has been questioned, since some authors have found that oncocytic follicular lesions called benign subsequently behave in a malignant fashion (20). This may be attributed to failure to recognize the nuclear atypia of malignancy in these neoplasms (12,18,21,22), but also partly to common challenges in the identification of invasive growth in follicular neoplasms (23)(24)(25)(26).…”
Section: Thyroid Follicular Nodular Disease and Adenomasmentioning
confidence: 99%
“…As in nononcocytic tumors, these neoplasms are classified as (i) minimally invasive oncocytic carcinoma (tumor capsular invasion only), (ii) angioinvasive encapsulated oncocytic carcinoma (angioinvasion with no widely invasive growth), and (iii) widely invasive oncocytic carcinoma (often angioinvasive) (31). Oncocytic lesions that have nuclear atypia but lack invasion fall into the category of Non-Invasive Follicular Tumor with Papillary-like nuclei (NIFTP) (35); however, this remains controversial since it has been reported that oncocytic tumors with follicular architecture and nuclear atypia that lack overt invasion in sections examined can metastasize (12,18,(20)(21)(22).…”
Section: Follicular-patterned Differentiated Thyroid Carcinomasmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, many have proposed different morphologic characteristics to distinguish between benign and malignant Hurthle cell tumors [3]. Recent molecular studies have shed light on the distinct oncogenic features of Hurthle cell carcinomas, suggesting that they represent a separate pathological entity from both Hurthle cell adenomas and follicular cell carcinomas [4,5]. The accurate preoperative diagnosis of these tumors is essential for appropriate management decisions.…”
Section: Introductionmentioning
confidence: 99%